Pengujian Aerodinamis Desain Mobil Listrik Kapasitas 12 Penumpang Menggunakan Software Solidworks 2020 - Khakim, Faisal; Sumbodo, Wirawan; Kriswanto, Kriswanto (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This study aims to analyze the aerodynamic performance of the 12-passenger electric car body design using a numerical simulation based on Computational Fluid Dynamics (CFD) with SolidWorks 2020 software. The vehicle body design was created using Autodesk Inventor and analyzed in a speed variation of 80 km/h to 100 km/h. The simulation results showed that the drag coefficient (Cd) value was in the stable range of 0.474 - 0.475 which indicates that the design has a fairly good aerodynamic performance for the shuttle vehicle class. Pressure distribution analysis shows an increase in maximum pressure and suction effect at the rear of the vehicle as speed increases. The airflow pattern also shows an increase in the turbulent zone (wake) behind the vehicle at high speeds which causes aerodynamic efficiency to decrease. Overall, this design shows optimal aerodynamic performance at medium speeds, and can be used as a reference for the development of future electric vehicles.